Do firm-level variables affect corporate governance quality and performance? Evidence from India. (2017) - Arora, Ashima; Bhandari, Varun
The importance of corporate governance (CG) gained widespread prominence as a means to boost corporate performance especially in the aftermath of global financial crisis of 2008 and some big corporate scams of Satyam and Reebok. Limited literature focussing on factors influencing CG quality guided this study towards the construction of CG Index (CGI), investigation of impact of firm-level variables on CGI and factors affecting performance of firms. The result relays that market capitalisation, R&D intensity and age of the firm have a significant positive impact on CGI compared with negative effect of performance. As expected, CGI, corporate social responsibility (CSR), advertising intensity, size and leverage demonstrate a significant impact on performance of the firms in both during and post-crisis periods. Our findings imply that companies having better governance and CSR framework provide an impetus for companies and regulators to further improve CG practices and firm's value gradually.